Effective treatment of the leaf eating caterpillar, Trilocha varians (LEPIDOPTERA: BOMBYCIDAE) with beauveria bassiana in combination with an insecticide under laboratory conditions - Muhammad Ramzan,; Mahreen Hanif,; Muqaddas Younas,; Syed Muhammad Farhan Bukhari,; Norasmah Basari, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Ficus benjamina (Moraceae) commonly called fig, is an ornamental plant planted alongside the canal, roads and inside the parks and academic institutes to increase their beauty. The aesthetic value of F. benjamina is declining due to attack of leaf eating caterpillar, Trilocha varians. The current study was conducted under laboratory conditions to determine the effect of Beauveria bassiana with and without the combination of insecticide (emmamectin benzoate) on 2nd and 3rd larvae of T. varians. Complete larval mortality (100%) of T. varians was recorded at the highest (2×105) concentration of Beauveria bassiana without insecticide after seven days of post treatments but when the B. bassiana treatment was conducted together with insecticide, the result showed 100% mortality of the second larval instar just after six days. The second instar larvae were more susceptible to all concentrations of fungus with and without the combination with insecticides (χ21,40 = 952.99, P<0.001). Even though both insecticide and fungus could become the best control for T. varians, it was proven that treatment with fungus together with insecticide showed faster effect. Hence, this finding should be tested under the field conditions in future.